ICT Integration in the English Learning Context for the Higher Education Students: Potencies and Issues - Purwati, Heni; Nain Difinubun, Tis’a (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
Information and communication technology (ICT) exists as a new trend in English language teaching and learning for recent years. This study aimed to explore the potencies and issues to the use of ICT in English language learning process. A descriptive qualitative research method was used to find out the phenomena of the use of ICT in an English language course for one semester. Sixty-three higher education students at a Health Polytechnic in Jayapura were the sample of this research. The data of this research were collected from questionnaire and Interview. The findings indicated that students have adequate knowledge about ICT tools and the use in English language learning activities. ICT has high potencies to be applied and developed due to its roles, benefits and students ‘attitudes toward the implementation of ICT in English class. Students gain the positive impact of using ICT both in offline and online English Class. The implementation of ICT in English teaching and learning process can improve English competency, promote the learning motivation, and provide variety in learning process, and flexibility in time and place. On the other hand, some factors such as the lack of ICT literacy, incompatibility of ICT Tools, cost, and error of internet connection become the challenges that diminish the efficacy of ICT deployment in the English learning process.